Design, Synthesis, and Anti-Proliferative Action of Purine/Pteridine-Based Derivatives as Dual Inhibitors of EGFR and BRAFV600E - Samar A. El-Kalyoubi; Hesham A. M. Gomaa; Elshimaa M. N. Abdelhafez; Mohamed Ramadan; Fatimah Agili; Bahaa G. M. Youssif (MDPI AG, 2023)
The investigation of novel EGFR and BRAFV600E dual inhibitors is intended to serve as targeted cancer treatment. Two sets of purine/pteridine-based derivatives were designed and synthesized as EGFR/BRAFV600E dual inhibitors. The majority of the compounds exhibited promising antiproliferative activity on the cancer cell lines tested. Compounds 5a, 5e, and 7e of purine-based and pteridine-based scaffolds were identified as the most potent hits in anti-proliferative screening, with GI50 values of 38 nM, 46 nM, and 44 nM, respectively. Compounds 5a, 5e, and 7e demonstrated promising EGFR inhibitory activity, with IC50 values of 87 nM, 98 nM, and 92 nM, respectively, when compared to erlotinib's IC50 value of 80 nM. According to the results of the BRAFV600E inhibitory assay, BRAFV600E may not be a viable target for this class of organic compounds. Finally, molecular docking studies were carried out at the EGFR and BRAFV600E active sites to suggest possible binding modes.